A role for β,β-xanthophylls in Arabidopsis UV-B photoprotection - Emiliani, Julia; D'Andrea, Lucio; Lorena Falcone Ferreyra, María; Maulión, Evangelina; Rodriguez, Eduardo; Rodriguez-Concepción, Manuel; Casati, Paula (Journal of experimental botany, 2018)
Carotenoids have a role in UV-B photoprotection in Arabidopsis thaliana and this requires β,β-xanthophylls, but not other plastidial isoprenoids. Abstract Plastidial isoprenoids, such as carotenoids and tocopherols, are important anti-oxidant metabolites synthesized in plastids from precursors generated by the methylerythritol 4-phosphate (MEP) pathway. In this study, we found that irradiation of Arabidopsis thaliana plants with UV-B caused a strong increase in the accumulation of the photoprotective xanthophyll zeaxanthin but also resulted in slightly higher levels of γ-tocopherol. Plants deficient in the MEP enzymes 1-deoxy-D-xylulose 5-phosphate synthase and 1-hydroxy-2-methyl-2-butenyl 4-diphosphate synthase showed a general reduction in both carotenoids and tocopherols and this was associated with increased DNA damage and decreased photosynthesis after exposure to UV-B. Genetic blockage of tocopherol biosynthesis did not affect DNA damage accumulation. In contrast, lut2 mutants that accumulate β,β-xanthophylls showed decreased DNA damage when irradiated with UV-B. Analysis of aba2 mutants showed that UV-B protection was not mediated by ABA (a hormone derived from β,β-xanthophylls). Plants accumulating β,β-xanthophylls also showed decreased oxidative damage and increased expression of DNA-repair enzymes, suggesting that this may be a mechanism for these plants to decrease DNA damage. In addition, in vitro experiments also provided evidence that β,β-xanthophylls can directly protect against DNA damage by absorbing radiation. Together, our results suggest that xanthophyll-cycle carotenoids that protect against excess illumination may also contribute to protection against UV-B.